Pengaruh Capital Intensity, Persistensi Laba dan Risiko Litigasi terhadap Konservatisme Akuntansi pada Perusahaan di Bidang Kesehatan yang Terdaftar di Bursa Efek Indonesia - Adinda Octaviani; Suwarno Suwarno (Universitas 45 Surabaya, 2024)
This study aims to analyze the effect of capital intensity, earnings persistence and litigation risk on accounting conservatism. The research population consists of companies in the health sector listed on the Indonesia Stock Exchange in 2020-2022. With the purposive sampling method, a sample of 16 companies or 48 observation data was obtained. The analysis method used is multiple linear regression analysis using the SPSS Statistics 25 program. The results of this study indicate that the capital intensity variable and litigation risk have no effect on accounting conservatism. Meanwhile, earnings persistence affects accounting conservatism.